Reactive Centre Loop Mutagenesis of SerpinB3 to Target TMPRSS2 and Furin: Inhibition of SARS-CoV-2 Cell Entry and Replication - Bowie, Andrew; Gewaid, Hossam (My University, 2022)
The SARS-CoV-2 virus can utilize host cell proteases to facilitate cell entry, whereby the Spike (S) protein is cleaved at two specific sites to enable membrane fusion. Furin, transmembrane protease serine 2 (TMPRSS2), and cathepsin L (CatL) are the major proteases implicated, and are thus targets for anti-viral therapy. The human serpin (serine protease inhibitor) alpha-1 antitrypsin (A1AT) shows inhibitory activity for TMPRSS2, and has previously been found to suppress cell infection with SARS-CoV-2. Here, we have generated modified serpin inhibitors with increased specificity for these cellular proteases. Using SerpinB3 (SCCA-1), a cross-class inhibitor of CatL, as a scaffold, we have designed and produced reactive centre loop (RCL) variants to more specifically target both furin and TMPRSS2. Two further variants were generated by substituting the RCL P7–P1 with the spike protein S1/S2 cleavage site from either SARS-CoV-2 alpha or delta (P681R) sequences. Altered inhibitory specificity of purified recombinant proteins was verified in protease assays, with attenuated CatL inhibition and gain of furin or TMPRSS2 inhibition, as predicted, and modified serpins were shown to block S protein cleavage in vitro. Furthermore, the serpin variants were able to inhibit S-pseudoparticle entry into A549-ACE2-TMPRSS2 cells and suppress SARS-CoV-2 replication in Vero E6 cells expressing TMPRSS2. The construct designed to inhibit TMPRSS2 (B3-TMP) was most potent. It was more effective than A1AT for TMPRSS2 enzyme inhibition (with an eighteen-fold improvement in the second order inhibition rate constant) and for blocking SARS-CoV-2 viral replication. These findings advance the potential for serpin RCL mutagenesis to generate new inhibitors, and may lead to novel anti-viral biological molecules.
PUBLISHED
Keywords: SARS-CoV-2; SerpinB3; TMPRSS2; furin; cathepsin L; antiviral; designer serpin